Paradoks Kesehatan Jantung Guru SMAN Kota Palu: Kepungan Gaya Hidup Berisiko Tinggi - Adhyanti, Adhyanti; Candriasih, Putu; Yusuf, A. Mukramin; Irawan, Andi Muh. Asrul; Ramadhan, Kadar (Bomba: Jurnal Pembangunan Daerah, 2025)
The health status of teachers in Palu City is currently in a "paradoxical" state. Although the prevalence of clinical heart disease and diabetes (high random blood sugar) remains very low at 1.8% each , there is a serious root problem in the form of widespread high-risk lifestyles. Data shows that 100% of teachers have insufficient physical activity , the majority suffer from cholesterol issues (56.3%) , and a significant portion are obese or overweight. This issue is strategic because teachers are a productive population and the pillars of education; a decline in their health will impact the quality of education and increase the state's financial burden through BPJS claims for catastrophic diseases in the future. The proposed solutions include structured healthy lifestyle intervention programs within the school environment and routine health screenings. The Education Office of Central Sulawesi Province and the Palu City Health Office are the primary actors responsible for implementing this policy.